2004
DOI: 10.1016/s1090-5138(03)00064-3
|View full text |Cite
|
Sign up to set email alerts
|

Student athletes claim to have more sexual partners than other students

Abstract: To cite this version:Charlotte Faurie, Dominique Pontier, Michel Raymond. Student athletes claim to have more sexual partners than other students. Evolution and Human Behavior, Elsevier, 2004, 25, pp.1-8. 10.1016/S1090-5138 (03) AbstractPhysical competition is widespread in human societies. Because performance in competitive sports can signal phenotypic quality and fighting ability, high level performance, especially on the part of men, is likely to be attractive to the opposite sex. We investigated the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 22 publications
(23 reference statements)
4
78
0
7
Order By: Relevance
“…However, it is assumed than on average, increasing numbers of partners is a reasonable proxy for success in obtaining the partners desired, especially if not accompanied by a reduction in time spent in a steady relationship. Moreover, number of sexual partners is often used as a measure of mating success in studies of this kind (Gangestad et al 2001;Faurie et al 2004). Number of children was also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is assumed than on average, increasing numbers of partners is a reasonable proxy for success in obtaining the partners desired, especially if not accompanied by a reduction in time spent in a steady relationship. Moreover, number of sexual partners is often used as a measure of mating success in studies of this kind (Gangestad et al 2001;Faurie et al 2004). Number of children was also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…This perception of promiscuity of male athletes appears to be grounded in reality. Athletes, especially males, appear to have more sexual partners than non-participants (Faurie et al, 2004;Nattiv et al, 1997), and high-level athletes (both male and female) reported more sexual partners than low level athletes (Faurie et al, 2004). Why do athletes, especially male athletes, have more sexual partners than non-participants, and why are they thus perceived as more promiscuous?…”
Section: Discussionmentioning
confidence: 99%
“…Faurie, Pontier, and Raymond (2004) compared the number of self-reported sex partners by male and female athletes to those of non-athletes. On average, both males and females who participated in sport reported more sexual partners than non-participants.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ritualised competitions, such as tennis, can also be thought of as cultural arenas for male intra-sexual competition. Evidence for sporting performance being important in mate choice comes from FAURIE et al (2004), who found that students who competed in sports had greater mating success than those that did not, as measured by self-reported numbers of sexual partners. Also, performance levels of athletes also positively correlated with mating success (FAURIE et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for sporting performance being important in mate choice comes from FAURIE et al (2004), who found that students who competed in sports had greater mating success than those that did not, as measured by self-reported numbers of sexual partners. Also, performance levels of athletes also positively correlated with mating success (FAURIE et al 2004). We therefore predicted that performance in cultural displays of tennis among males would be adversely affected by a transition to marriage.…”
Section: Introductionmentioning
confidence: 99%